Effects of female body size and age and male mating status on male combat in Anastatus disparis (Hymenoptera: Eupelmidae). (11th May 2020) - Liu, Peng‐Cheng; Wei, Jian‐Rong; Han, Xuan; Hao, De‐Jun; Wang, Zi‐Yi; Wang, Zi‐Qi; Wang, Qiong
Abstract : 1. Aggressive behaviour is widely exhibited by animals to acquire important resources and usually shows a dangerous or nondangerous pattern. Dangerous fighting patterns are usually characterized by fights ending with contestants being severely injured or killed. Resource value is an important nonstrategic factor influencing fighting behaviour. Studies of many species addressing nondangerous fighting behaviour have shown that when resource values change, organisms usually adjust their fighting behaviour accordingly. Only a few species show dangerous fighting patterns. Thus, few relevant studies have addressed how variation in resource value affects aggression with a dangerous fighting pattern. 2. Here, an egg parasitoid wasp, Anastatus disparis, which exhibits a dangerous fighting pattern to acquire mating opportunities, was used as an experimental model to study the adjustment of fighting behaviour resulting from a change in resource value. 3. Our results show that the female properties of body size and age affect their objective resource value and that males increased their fighting intensity for relatively large and young females. However, male mating status in A. disparis may not influence the subjective value of mate resources, and fighting intensity did not significantly differ between mated and virgin males. In addition, the number of times a male had previously mated had no significant effect. These results suggest that mating opportunities are important for both virgin and mated males, resulting in neither of them showing any adjustment in fighting for mating opportunities. 4. Generally, A. disparis males with extreme fighting patterns adjust their fighting behaviour according to the variation in resource value, which avoids the meaningless costs of injury and death. Abstract : Anastatus disparis males with extreme fighting patterns adjust their fighting behaviour according to the variation in the resource value. Female properties of body size and age affect objective resource value and that males increased their fighting intensity for relatively large and young females. Male mating status in A. disparis may not influence the subjective value of mate resources, and fighting intensity did not significantly differ between mated and virgin males.